A new approach to overcoming antibiotic-resistant bacteria: Traditional Chinese medicine therapy based on the gut microbiota - Xue, Peng; Sang, Rui; Li, Nan; Du, Siyuan; Kong, Xiuwen; Tai, Mingliang; Jiang, Zhihao; Chen, Ying (Frontiers in Cellular and Infection Microbiology, 2023)
With the irrational use of antibiotics and the increasing abuse of oral antibiotics, the drug resistance of gastrointestinal pathogens has become a prominent problem in clinical practice. Gut microbiota plays an important role in maintaining human health, and the change of microbiota also affects the activity of pathogenic bacteria. Interfering with antibiotic resistant bacteria by affecting gut microbiota has also become an important regulatory signal. In clinical application, due to the unique advantages of traditional Chinese medicine in sterilization and drug resistance, it is possible for traditional Chinese medicine to improve the gut microbial microenvironment. This review discusses the strategies of traditional Chinese medicine for the treatment of drug-resistant bacterial infections by changing the intestinal microenvironment, unlocking the interaction between microbiota and drug resistance of pathogenic bacteria.